Mastering your fellowship: Part 2, 2022 - Mergan Naidoo; Klaus B. von Pressentin; Tasleem Ras; Ts'epo Motsohi (South African Family Practice)
The series, ‘Mastering your Fellowship’, provides examples of the question format encountered in the written and clinical examinations, Part A of the Fellow of the College of Family Physicians South Africa (FCFP SA) examination. The series is aimed at helping family medicine registrars prepare for this examination. Model answers are available online.